2015
DOI: 10.5194/acp-15-12611-2015
|View full text |Cite
|
Sign up to set email alerts
|

Variations of surface ozone at Ieodo Ocean Research Station in the East China Sea and the influence of Asian outflows

Abstract: Abstract. Ieodo Ocean Research Station (IORS), a research tower ( ∼ 40 m a.s

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…The Amazon Tall Tower Observatory (ATTO) was established ∼ 150 km northeast of the city of Manaus, Brazil for comprehensive studies of meteorology (Morton et al, 2014;Quesada et al, 2012;Sun et al, 2011), trace gases (Andreae et al, 2012;Trebs et al, 2012), aerosol compositions (Andreae et al, 2012;Yáñez-Serrano et al, 2018;Rizzo et al, 2013;Saturno et al, 2018), and ecology (Pöhlker et al, 2019;Quesada et al, 2012) to investigate long-term trends of the Amazonian hydrological and biogeochemical cycling linked with the human perturbation (Andreae et al, 2015). The 304 m tower of the Zotino Tall Tower Observatory (ZOTTO) in central Siberia serves as a basis for monitoring biogeochemical gases (Chi et al, 2013;Mikhailov et al, 2017;Winderlich et al, 2010), aerosol characteristics (Chi et al, 2013;Heintzenberg et al, 2011;Mikhailov et al, 2017) and atmospheric transport (Mikhailov et al, 2017) at a wide range of spatial and temporal scales.…”
Section: Introductionmentioning
confidence: 99%
“…The Amazon Tall Tower Observatory (ATTO) was established ∼ 150 km northeast of the city of Manaus, Brazil for comprehensive studies of meteorology (Morton et al, 2014;Quesada et al, 2012;Sun et al, 2011), trace gases (Andreae et al, 2012;Trebs et al, 2012), aerosol compositions (Andreae et al, 2012;Yáñez-Serrano et al, 2018;Rizzo et al, 2013;Saturno et al, 2018), and ecology (Pöhlker et al, 2019;Quesada et al, 2012) to investigate long-term trends of the Amazonian hydrological and biogeochemical cycling linked with the human perturbation (Andreae et al, 2015). The 304 m tower of the Zotino Tall Tower Observatory (ZOTTO) in central Siberia serves as a basis for monitoring biogeochemical gases (Chi et al, 2013;Mikhailov et al, 2017;Winderlich et al, 2010), aerosol characteristics (Chi et al, 2013;Heintzenberg et al, 2011;Mikhailov et al, 2017) and atmospheric transport (Mikhailov et al, 2017) at a wide range of spatial and temporal scales.…”
Section: Introductionmentioning
confidence: 99%
“…Meteorological parameters, especially winds that are important for O 3 outflow, also exhibit variations on different timescales (Chang et al, 2000;Ding et al, 2008b;Sun et al, 2009;Zhang and Guo, 2010;Hirahara et al, 2012). Large IAVs in the East Asian summer monsoon (EASM) have been reported in previous studies (Zhu et al, 2012;Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 87%
“…They also reported that the decrease in ozone-rich Eurasian airflow reaching the eastern North Pacific in spring in the 2000s was attributed to more frequent La Niña events. Most of the models in the Coupled Model Intercomparison Project Phase 3 (CMIP3) predicted that the Asian jet would be intensified on its equatorward side by the end of the 21st century (Zhang and Guo, 2010;Hirahara et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Asian O 3 outflow exhibits seasonal variations (Liu et al, 2002;Han et al, 2015). Using a global 3-D chemical transport model GEOS-Chem, Liu et al (2002) simulated the seasonal variations of the Asian outflow flux of O 3 over the Pacific, which was defined as the eastward flux integrated for the tropospheric column through a wall located at 25 150° E between 10° N and 60° N. They found that the Asian O 3 outflow flux reached the maximum in early spring (March) and the minimum in summer (July).…”
Section: Introductionmentioning
confidence: 99%
“…Using a global 3-D chemical transport model GEOS-Chem, Liu et al (2002) simulated the seasonal variations of the Asian outflow flux of O 3 over the Pacific, which was defined as the eastward flux integrated for the tropospheric column through a wall located at 25 150° E between 10° N and 60° N. They found that the Asian O 3 outflow flux reached the maximum in early spring (March) and the minimum in summer (July). Han et al (2015) examined O 3 measurements at Ieodo Ocean Research Station, which was located in the East China Sea and regarded as an ideal place to observe Asian outflow without local effects. They reported that the seasonal variation of O 3 was distinct, with a minimum in August and two peaks in April and October, and was greatly affected by the seasonal wind pattern over East Asia.…”
Section: Introductionmentioning
confidence: 99%